Evaluation of energy supplements in dual purpose cows in a silvopastoral system - GALVEZ-LUIS, JOEL; ARRIAGA-JORDÁN, CARLOS MANUEL; YONG-ÁNGEL, GILBERTO; MACIAS-FARRERA, PATRICIA; SÁNCHEZ-VALDÉS, JAIR JESÚS; LÓPEZ-GONZÁLEZ, FELIPE (The Indian Journal of Animal Sciences, 2023)
The objective was to evaluate the effect of three energy concentrates on dietary nitrogen utilisation efficiency, milk production and milk composition. Twelve dual-purpose cows fed in a silvopastoral (SSP) system with Leucaena leucocephala and Digitaria swazilandensis were fed four treatments, supplemented with 25 MJ/cow/day of sorghum, molasses and gluconeogenic precursors, plus the control treatment, using a 4×4 Latin square experimental design with three replicates and experimental periods of 14 days and a total duration of 56 days. No significant differences were found for milk yield, milk chemical composition and milk urea nitrogen (MUN). No significant differences were found for cow live weight and dry matter intake. Forage analysis showed significant difference for crude protein (CP) concentration. There was no significant difference for average values of dry matter (DM) yield, neutral detergent fibre (NDF), acid detergent fibre (ADF), lignin and in vitro DM matter. For Leucaena, a significant difference was found only in DM yield, with period 4 being the highest yielding period compared to periods 1, 2 and 3. There was no significant difference for CP, NDF, ADF, lignin and in vitro DM digestibility. This work allows to understand the interaction of CP metabolism with DM. It is concluded that SSP provides sufficient dietary energy to cows in production for dual-purpose cows ranching.